2023
DOI: 10.3389/fvets.2023.1086001
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the epidemiology of Mycobacterium bovis using whole-genome sequencing combined with environmental and demographic data

Abstract: When studying the dynamics of a pathogen in a host population, one crucial question is whether it transitioned from an epidemic (i.e., the pathogen population and the number of infected hosts are increasing) to an endemic stable state (i.e., the pathogen population reached an equilibrium). For slow-growing and slow-evolving clonal pathogens such as Mycobacterium bovis, the causative agent of bovine (or animal) and zoonotic tuberculosis, it can be challenging to discriminate between these two states. This is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…WGS was used to gain insights into the epidemiology of M. bovis in Cameroon. A total of 91 high-quality sequences of M. bovis were analyzed with respect to environmental, demographic, ecological, and cattle movement data to generate inferences using phylodynamic models [ 106 ]. The findings suggested that M. bovis in Cameroon was slowly expanding its epidemiological range over time; therefore, endemic stability was unlikely.…”
Section: Wgs In Epidemiological Tracking Of Bacterial Pathogens In Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…WGS was used to gain insights into the epidemiology of M. bovis in Cameroon. A total of 91 high-quality sequences of M. bovis were analyzed with respect to environmental, demographic, ecological, and cattle movement data to generate inferences using phylodynamic models [ 106 ]. The findings suggested that M. bovis in Cameroon was slowly expanding its epidemiological range over time; therefore, endemic stability was unlikely.…”
Section: Wgs In Epidemiological Tracking Of Bacterial Pathogens In Co...mentioning
confidence: 99%
“…The findings suggested that M. bovis in Cameroon was slowly expanding its epidemiological range over time; therefore, endemic stability was unlikely. The authors concluded that the use of WGS as part of surveillance would vastly improve our understanding of disease ecology and control strategies [ 106 ].…”
Section: Wgs In Epidemiological Tracking Of Bacterial Pathogens In Co...mentioning
confidence: 99%
“…WGS of M. bovis has so far been used to characterise clusters of transmission [2024], and quantify rates of between-species transmission [12, 15, 20, 25–30]. Our interest here is in the more forensic problem of identifying “who-infected-whom” in a population of infected hosts, and whether WGS can be effectively employed to better discriminate between possible animal-to-animal transmission pathways.…”
Section: Introductionmentioning
confidence: 99%